1998
DOI: 10.1038/bjc.1998.557
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and evaluation of serum anti-p53 antibody levels in patients with lung cancer at its initial presentation: a prospective study

Abstract: Summary Anti-p53 antibodies in sera are known to be products of the host immune response to mutated p53 protein, and are present in some patients with various types of cancer. In this study, we measured serum anti-p53 antibody levels in 52 patients with lung cancer and 63 normal volunteers to determine the relationship between anti-p53 antibody level and clinical features of lung cancer patients. Anti-p53 antibody level was measured by an enzyme-linked immunosorbent assay and expressed as an anti-p53 antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For the studies with single autoantibody, the 31 articles (with 38 tests) included participants from 8 countries ( Table 1 ). The most studied populations were Chinese [ 35 , 45 , 65 , 75 , 79 , 85 , 87 – 92 , 94 ] and Japanese [ 68 , 77 , 82 , 83 , 89 , 96 ], followed by American [ 38 , 71 – 73 ], Italian [ 78 , 80 , 93 ], and German [ 76 , 95 ].The earliest study was from 1985, and anti-CSLEX1 antibody was the first tumor-associated autoantibody to be reported in patients with LC. The sample size of the included trials ranged from 28 to 813 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…For the studies with single autoantibody, the 31 articles (with 38 tests) included participants from 8 countries ( Table 1 ). The most studied populations were Chinese [ 35 , 45 , 65 , 75 , 79 , 85 , 87 – 92 , 94 ] and Japanese [ 68 , 77 , 82 , 83 , 89 , 96 ], followed by American [ 38 , 71 – 73 ], Italian [ 78 , 80 , 93 ], and German [ 76 , 95 ].The earliest study was from 1985, and anti-CSLEX1 antibody was the first tumor-associated autoantibody to be reported in patients with LC. The sample size of the included trials ranged from 28 to 813 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…We identified a trend between circulating AAbs to p53 and the presence of somatic tumor TP53 mutations. Further validation with a larger cohort of samples and comprehensive sequencing of distant metastatic sites is warranted (Fig. B).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently p53 mutations detectable in tumour samples have been shown to be not only an independent marker for poor outcome in resectable stage I NSCLC (Harpole, 1995), but also to correlate with nodal involvement and thus shorter survival (Marchetti et al, 1993). In NSCLC there is a prevalence of p53 antibodies of around 24% correlated with a much higher rate of p53 mutation, of the order of 60-70% (Schlichtholz et al, 1992;Winter et al, 1992;Wild et al, 1995;Komiya et al, 1997;Rosenfeld et al, 1997;Bergqvist et al, 1998;Iizasa et al, 1998;Laudanski et al, 1998;Mitsudomi et al, 1998;Segawa et al, 1998). Studies have shown a decrease in levels of p53-Abs in patients treated for lung cancer (Zalcman et al, 1998).…”
mentioning
confidence: 99%